The dendrochronologically dated horizons (173–230/231 AD) of Cham-Hagendorn (Canton Zug, Switzerland) - Winet, Ines (Rei Cretariae Romanae Fautorum Acta, 2017)
In 1944/45, the remains of a Roman water mill were discovered in Cham-Hagendorn. In 2003/2004 the site was investigated anew. Thereby, the archaeologists uncovered earlier Roman remains. A smithy (Horizon 1a) is followed by a two-phase sanctuary (Horizon 1a/Horizon 1b). The water mill (Horizon 2) is then replaced by a younger smithy (Horizon 3). The site’s last Roman horizon (Horizon 4) cannot be defined further. Thanks to the recent excavations, all structures were able to be fitted into a stratigraphical framework. The site was situated by a stream, which continually flooded thus destroying the aforementioned structures. In the cases proven, the rebuilding usually led to a change in the site’s function.